Molecular differentiation and antifungal susceptibilities of Candida parapsilosis isolated from patients with bloodstream infections - Tay, S. T.; Na, S. L.; Chong, J. (Microbiology Society, 2009)
The genetic heterogeneity and antifungal susceptibility patterns of Candida parapsilosis isolated from blood cultures of patients were investigated in this study. Randomly amplified polymorphic DNA (RAPD) analysis generated 5 unique profiles from 42 isolates. Based on the major DNA fragments of the RAPD profiles, the isolates were identified as RAPD type P1 (29 isolates), P2 (6 isolates), P3 (4 isolates), P4 (2 isolates) and P5 (1 isolate). Sequence analysis of the internal transcribed spacer (ITS) gene of the isolates identified RAPD type P1 as C. parapsilosis, P2 and P3 as Candida orthopsilosis, P4 as Candida metapsilosis, and P5 as Lodderomyces elongisporus. Nucleotide variations in ITS gene sequences of C. orthopsilosis and C. metapsilosis were detected. Antifungal susceptibility testing using Etests showed that all isolates tested in this study were susceptible to amphotericin B, fluconazole, ketoconazole, itraconazole and voriconazole. C. parapsilosis isolates exhibited higher MIC(50) values than those of C. orthopsilosis for all of the drugs tested in this study; however, no significant difference in the MICs for these two Candida species was observed. The fact that C. orthopsilosis and C. metapsilosis were responsible for 23.8 and 4.8 % of the cases attributed to C. parapsilosis bloodstream infections, respectively, indicates the clinical relevance of these newly described yeasts. Further investigations of the ecological niche, mode of transmission and virulence of these species are thus essential.